METHODICAL ASPECTS OF THE ANALYSIS OF THE WORLD AND NATIONAL TOURIST INDUSTRY - V. Yermachenko (Економіка розвитку, 2012)
The methodology of counting of tourist flows in Ukraine is based on the three-dimensional model, where the types of tourism (inbound, outbound and domestic) form the broader categories (international, national and tourism within the borders of a country). The estimation of the national tourism sphere output presented in the world databases is more detailed but hard to be matched with the inner concept. The precise analysis of the WTTC methodology clears out that the same approach is used in the evaluation of countries’ profiles, only with more or less inclination to domestic or international activity.According to the primary data, visitor exports exceeds the expenditure on outbound travel and domestic expenditure, but the direct contribution of travel and tourism to the GDP represents that the adjusted income from inbound tourism (foreign visitor spending) made 13.2 bn UAH and domestic spending 11.4 bn UAH (total GDP 24.6), when expenditure on outbound travel was estimated in 33.1 bn UAH (2011 data, Ukraine). So, the pure industry received losses in 33.1 – 24.6 = 8.5 bn UAH, but the net balance of money flows cannot be measured using the same indicators, as the expenses of supply chain (purchases by tourism providers) include both imports and intermediate consumption in domestic market. The researcher needs to apply to the payments balance in order to evaluate the net income of the tourist industry.The official data of tourist flows of Ukraine can be regarded as rather contradictory due to the procedure of gathering the information. International organisations pay more attention to the evaluation of income and money transfers when assessing the functioning of national economy or a separate industry, but the resultant figures which describe the sphere of tourism in Ukraine are predominantly composed by the number of trips.Expert judgements give unfavourable forecasts for revenues in the international tourist market of Ukraine, as more and more operations are transferred to a hidden sector (legal activity which cannot be followed), and personal expenses are constantly increasing but are not calculated. In Ukraine, households’ income outflows for the benefit of other host countries are one of the factors of budget deficit as the money of possible secondary sector circulates in foreign economies.The correlation between the values of tourist industry contribution to the GDP and the shares of visitors export in total tourism expenditure is better described by an exponential model when the share of visitor exports in total expenditures don’t exceed 70 %, and by a polynomial model when visitor exports exceed 70 % of total tourist expenditures. The data taken from 181 national economy demonstrate that the contribution of international tourism receipts to the total gross income (which contains expenditures of outbound, domestic and foreign visitors) is not a crucial factor influencing the share of T&T Direct Contribution to the GDP for the majority of the countries. The stability of tourism market in a state is supported by the domestic consumption and reasonable ratio between inbound and outbound flows. The investigated countries were arranged almost equally by the share of domestic expenditures in direct T&T contribution to the GDP (distribution is close to normal), but the share of outbound travel expenditures was displaced in general to the maximum. The problem of counting of individual tourists via organised trips and private money transfers in both sides is now the common problem of tourism economy. The huge increase in electronic payment systems operations in the CIS countries has been following the same trends in developed markets. The reduction of the complexity of international private payments forces the development of unassisted tourism sector and raises the volume of uncontrolled by the government foreign economic operations.